Adaptive Ambient Temperature Control Based on Employee Activity on Workstation - Rajarshi Bhattacharya (International Journal of Advanced Science and Technology, 2020)
Over the last few decades, organizations have realized the effects that ambient factors have on employee productivity and performance, and have taken these factors into account while designing a workspace and commissioning a new workstation. However, challenges are still encountered in the process, since different employees have different requirements of these ambient factors like the office temperature to ensure optimal productivity and often the intended temperature is not environment friendly and causes more power consumption. Taking into consideration the different requirement from different employees and also taking the high power consumption by air conditioning systems into account, in a work environment a uniform ambient temperature may not be the best feasible solution. This paper aims to design a system that monitors employee performance in real time, and changes the workstation temperature to ensure optimal performance for the employee. The system also takes the requirements of different demographics into account, and can cater to the needs of a global workforce. The system was designed after taking into account several researches that has been done in this field. The system designed works over the internet and runs as a software on a Microsoft Windows operating system, and connects to the Heating, Ventilation and Air Conditioning (HVAC) system to change the temperature to optimal level.